Synthesis of New 2,3-Disubstituted Quinoxalines from 4,4-Substituted Chalcones - Deshmukh, A.Y.; Raghuwanshi, P.B.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
4'-Chlorochalcone (Ia), 4'-chloro-4-methoxychalcone (Ib), 4'nitrochalcone (Ic) and 4' -nitro-4-methoxychalcone (Id) react with bromine in acetic acid to give chalcone dibromides (lIa-d). The chalcone dibromides (IIa-d) condense with benzene 1,2-diamine (BDA) in presence of few drops of concentrated H2SO4 in methanel medium to affords 2,3-disubstituted quinoxalines (IIIa-d). The structures of these compounds were confirmed by analytical and spectral data.